(3eHGOF GdGbJUGO Gdcdj (B:s (3cja jYed GdEbJUGO aj GdfXQjI hGdJWHjb (B/s - (3GdYjSi, fRGQ SYO GdOjfs ((3YeGf(B: s (3GdOGQ GdYdejI GdOhdjI ddfTQ h OGQ GdKbGaI ddfTQ(B, s, 2001)
(3Yde GdGbJUGO,GdSeGJ GdCSGSjI dYde GdGbJUGO,GdENJjGQ Hjf GdHOGFd,NUGFU GdGbJUGO GdMOjK,BdjI GdShb,OhQ GdMcheGJ aj GdfTGW GdGbJUGOj,MSGHGJ GdfGJL Gdbhej,GdJbdHGJ GdGbJUGOjI,JaSjQ GdJbdHGJ GdGbJUGOjI,GdJhGRf aj GdfXQjI GdcjfRjI,GdSjGSI GdeGdjI,GdfbhO hGdeUGQa,GdSjGSI GdfbOjI,GdSjGSGJ GdeGdjI hGdfbOjI ef GdfXQjI Edi GdJWHjb,Gdfeh GdGbJUGOj hGdJfejI GdGbJUGOjIs
(3HHdjhZQGajG U(B.391s
Keywords: (3GdGbJUGO Gdcdjs; (3GdJfejI GdGbJUGOjIs